Empresa y Estado en el Perú El modelo de responsabilidad social: el caso Doe Run en La Oroya - Pinto Herrera, Honorio (2007)
The articlc discusses the managerial model known as Corporate Socia! Responsibilitv (CSRj in the metollurgical mining industry 0/1(/ thc casé' of Doe RUI1 Peru (IJRP), ('SR is defincd. the 1)(Ji/'/[ofviev: ofsonu: authors srecializing in this topic is presented, a summary o/DRP programs and activities on CSR is introduced and finallv. some critica! observations are stated 0// tite behoviour v/rile mining - metallurgical (:OIll/}{1II_1' in its rclation with tlu: I'eruvian State. Theobjective is lo denionstrate the existing divorce betwcen thcp